1998
DOI: 10.1164/ajrccm.157.6.9710075
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Survival in Patients with Diffuse Panbronchiolitis Treated with Low-dose Erythromycin

Abstract: Diffuse panbronchiolitis (DPB) is a chronic inflammatory disease of the airways with a high rate of mortality despite treatment with a combination of antibiotics and the use of supportive therapy such as oxygen administration. Low-dose erythromycin therapy (EM) (400 to 600 mg/d) has been found to improve the survival of patients with DPB, and most patients with DPB in Japan have been treated with this erythromycin regime since 1984. The purpose of this study was to evaluate the effects of treatment with erythr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
371
0
6

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(382 citation statements)
references
References 14 publications
5
371
0
6
Order By: Relevance
“…11,37 Macrolides have been shown to improve outcome in panbronchiolitis. 38,39 Their beneficial effects are considered to be due to their anti-inflammatory rather than anti-bacterial activities. [40][41][42] Although there has been no report of macrolide use in BO, their mechanisms of action and relatively minor adverse effects warrant a clinical trial.…”
Section: Treatmentmentioning
confidence: 99%
“…11,37 Macrolides have been shown to improve outcome in panbronchiolitis. 38,39 Their beneficial effects are considered to be due to their anti-inflammatory rather than anti-bacterial activities. [40][41][42] Although there has been no report of macrolide use in BO, their mechanisms of action and relatively minor adverse effects warrant a clinical trial.…”
Section: Treatmentmentioning
confidence: 99%
“…Given their favourable bioavailability via the oral route, excellent tissue penetration and broad efficacy against many lung pathogens (most Gram-positive and some Gram-negative bacteria, mycobacteria, Chlamydia, Mycoplasma and Legionella species), macrolides are widely used as first-line agents in the therapy of respiratory infections [2], although there is a concern that long-term administration of macrolides can promote antimicrobial resistance [3]. In recent years, there has been an increasing interest in the potential immunomodulatory properties of macrolides following the observation of the effectiveness of erythromycin in diffuse panbronchiolitis (DPB), an idiopathic disease found almost exclusively in the Far East and characterised by chronic recurrent bronchiolitis and peribronchiolitis with inflammatory infiltration of the small airways [4]. The immunomodulatory effects of macrolides, which are only seen with 14-(erythromycin, clarithromycin and roxithromycin) and 15-members (azithromycin) [5], may take several weeks to manifest, and include reduced airway mucus secretion and viscosity [6] and decreased airway neutrophil accumulation through a reduction in pro-inflammatory cytokines expression and adhesion molecule production [7][8][9] (fig.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on ERM sub-MIC efficiency in reducing P. aeruginosa VIFs in vivo (Fujii et al, 1995;Kudoh et al, 1998) and in vitro (Kita et al, 1991;Kobayashi, 1995;Sofer et al, 1999) led us to examine its efficacy in presence of the osmoprotectant Ch (which is released in tissues damaged by P. aeruginosa (Chen et al, 2005)) and of Et, both of which increase P. aeruginosa VIF formation. P. aeruginosa cultures were grown for 3 days to obtain peak levels of lectins (Gilboa-Garber, 1982), proteases and haemolysins, and post-peak pyocyanin and HSL activities (Katri and Gilboa-Garber, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, an important improvement in patient health has been attained by long-term (years) treatment with erythromycin (ERM) or other macrolides at subinhibitory concentration (sub-MIC). This treatment reduces virulence without bacterial eradication (Fujii et al, 1995;Kudoh et al, 1998). Therefore, it has been suggested that at sub-MIC, ERM does not inhibit protein synthesis in exponentially growing cells (by binding to 50S ribosomal subunit), but functions in the stationary phase following the gene expression shift (Wagner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%